The Duogynon controversy and ignorance production in post-thalidomide West Germany - Nemec, Birgit; Olszynko-Gryn, Jesse (Reproductive biomedicine & society online, 2022)
This article examines the West German controversy over Duogynon, a 'hormone pregnancy test' and the drug at the centre of the first major, international debate over iatrogenic birth defects in the post-thalidomide era. It recovers an asymmetrical power struggle over the uneven distribution of biomedical knowledge and ignorance (about teratogenic risk) that pitted parent-activists, whistleblowers and investigative journalists against industrialists, scientific experts and government officials. It sheds new light on the nexus of reproduction, disability, epidemiology and health activism in West Germany. In addition, it begins to recover an internationally influential discourse that, in the post-thalidomide world, seems to have resuscitated antenatal drug use as safe until proven harmful.
Gesehen am 29.05.2023